Analisis Perancangan Sia Kas Menggunakan Software Microsoft Access 2019 (Studi Kasus Pada Pt Bendara Empat Logistik) - Muhammad Rachman Alghaniy; Rendra Trisyanto (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2022)
The Accounting Information System is an important part of a company. SIA must be based on certain standards to ensure quality. Cash accounting information systems are one of the most important types of business processes. Cash is the most liquid asset, so it needs to becontrolled properly in order to avoid irregularities. This research will aim to create a Cash Application System that will help the SIA Cash business process the subject of this research. The research method used is qualitative descriptive from the data collected in the form of interviews, documentation files, and observations. In designing this research application, the System Development Life Cycle (SDLC) method was assisted to analyze the condition of the current AIS. As an application system development, DBMS software is a strict software for designing applications and processing data. this study uses Microsoft Access 2019. The application system is based on the prototype needed by the subject of this research. The output generated from this application is in the form of invoice creation information, order reports, and cash flow reports. Due to SIA's business processes that have not been maximized, the Cash application system was created to support the existing system according to the needs of the research subject.